Innovation in Education: Transition for Enrolled Nurses - Downie, Jill; Horner, Barbara (Southern Cross University, 2002)
This paper discusses an initiative for qualified Enrolled Nurses, particularly those in rural Western Australia, to complete an educational transition to Registered Nurse. The discussion outlines one innovative model involving a partnership between educational institutions to address the needs of this student group. The course was developed in response to an extension of a curriculum review of the Bachelor of Science (Nursing) in 1999. The key to the success of the program, and what makes it differ from other distance education courses for Enrolled Nurses upgrading their qualifications to Registered Nurse is the role and commitment of the mentors in the Satellite Learning Centres around the State who form this important partnership. The promotion of student support mechanisms through the Centres has been a positive aspect of the course, as this vulnerable group of students often struggle to complete tertiary studies. The additional pressures of family responsibilities and work commitments, making study a difficult option, compound this. However, the challenge for universities is to continue to provide Enrolled Nurses with an opportunity to embark on tertiary study programs that are accessible, flexible, and innovative, particularly for those students in rural Australia.